Charge-switchable nanocapsules with multistage pH-responsive behaviours for enhanced tumour-targeted chemo/photodynamic therapy guided by NIR/MR imaging. Issue 20 (15th May 2018) - Zhou, Jia; Li, Tianliang; Zhang, Chunlei; Xiao, Junyuan; Cui, Daxiang; Cheng, Yingsheng
Abstract : Interaction of charge-switchable and multistage pH-responsive nanocapsules with MGC-803 cells at tumor site. Abstract : Multifunctional nanoplatforms have been developed into advanced drug delivery systems for cancer therapy. In this study, we report a charge-switchable nanocapsule with multistage pH-responsive behaviors. First, DOX-encapsulated and oleylamine-embedded hollow structures with a diameter of 132 ± 21 nm are prepared via the double emulsion method. Subsequently, the hollow structures are encompassed by Gd-DTPA-, chlorin e6 (Ce6)-, and folate (FA)-modified BSA to form tumour-targeted, dual NIR/MR imaging-guided and chemo–photodynamic therapeutic nanoplatforms. Importantly, the nanocapsule can intelligently switch its surface charge to positive under mildly acidic conditions (pH 6.5) with no release of Ce6 and DOX, which is confirmed by ξ-potential and cumulative release measurements. Moreover, confocal imaging pictures demonstrate that acid-sensitive DOX sealed in nanocapsules is progressively released into the nuclei of MGC-803 cells. These advantages as well as FA-targeting facilitate effective endocytosis and synergistic therapeutic efficacy. Selective tumour accumulation and long tumour retention time are further indicated by NIR/MR in vivo imaging. In addition, excellent therapeutic efficacy combined with chemotherapy (DOX) and photodynamic therapy (PDT) is observed with the tumour eventually ablating at the 15th day. All results demonstrate that the as-prepared nanocapsules hold great potential for clinical cancer theranostics.